Wistar Male Rats (Rattus norvegicus domestica) Are Aware of Their Dimensions - Ivan A. Khvatov; Polina N. Ganza; Alexander N. Kharitonov; Maria V. Samuleeva (Animals)
Body size awareness is the ability of animals to consider the size of their bodies when interacting with environmental objects. It is one of the manifestations of body self-awareness. We studied body size awareness in laboratory rats of Wistar strain. In the experiment, rats had to pass through one of three holes in a partition to reach the bait. In each trial, the shape, size, and position of the holes varied. The task of the first experiment was to establish whether rats prefer to pass through the larger holes, given that all the three were penetrable for their bodies. The task of the second experiment was to establish whether rats can choose the only penetrable hole while the other two were of a greater area but impenetrable. The results of the first experiment showed that the rats did not show a preference for larger holes. The results of the second experiment showed that rats can make the first approach and subsequent penetration immediately into the only penetrable hole even before the tactile contact with the partition. Thus, rats can consider the size of their own body when solving the task of penetrating into a hole, which is a sign of body size awareness. These results enrich our general understanding of the phenomenon of body self-awareness.